2010
DOI: 10.1155/2010/759645
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposure to Emissions from Petrochemical Sites and Lung Cancer: The Lower Mississippi Interagency Cancer Study

Abstract: To investigate potential links between environmental exposure to petrochemical plant emissions and lung cancer, a population-based case-control study (LMRICS) was conducted in eleven Louisiana parishes bordering the Mississippi River. Cases and age, gender, and race-matched controls were interviewed regarding potential risk factors. Residential history was geocoded to provide indices of long-term proximity to industrial sites. Cases were more likely to have lived near a petrochemical site. Models adjusted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Cancer Alley stretches approximately 100 miles from Baton Rouge to New Orleans in southeastern Louisiana (Figure A1, see Appendix). The region accounts for approximately 25% of the nation’s petrochemical production, consisting of over 130 plants, refineries, landfills, and factories [16]. Socioeconomic status (SES) data in Cancer Alley reflects low levels of income and high levels of poverty and illiteracy [17].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer Alley stretches approximately 100 miles from Baton Rouge to New Orleans in southeastern Louisiana (Figure A1, see Appendix). The region accounts for approximately 25% of the nation’s petrochemical production, consisting of over 130 plants, refineries, landfills, and factories [16]. Socioeconomic status (SES) data in Cancer Alley reflects low levels of income and high levels of poverty and illiteracy [17].…”
Section: Introductionmentioning
confidence: 99%
“…As previous literature has focused only on the adverse effect of the petrochemical industry on particular health problems, this study provides valuable information on the impact of a petrochemical industry on local residents’ life expectancies [3,9,23]. Our results also indicate that the impact of industrialisation on life expectancy could start 3–5 years after the facilities start running (intermittent industrialisation stage) for the whole population and the older population.…”
Section: Discussionmentioning
confidence: 62%
“…Most of the previous literature reported negative effects of petrochemical emissions on neighboring residents’ health, which might explain the smaller increase in life expectancies in the industrialized county [3-9,24,25]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case-control study on cancer risk associated to residents in the area surrounding petrochemical plants in Brindisi showed a moderate increase in risk, although not statistically significant, for lung, bladder and lymphohaematopoietic neoplasms (Belli et al 2004). Many studies suggested association between cancer incidence and residential proximity to petrochemical plants but without statistical significance (Wilkinson et al 1999;Axelsson et al 2010;Simonsen et al 2010), whereas, an analysis of matched geographical areas in Spain suggested a possible increased risk of non-Hodgkin lymphoma mortality among populations residing in the vicinity of refineries (Ramis et al 2012).…”
Section: Introductionmentioning
confidence: 99%